2021
DOI: 10.3390/ijerph18094985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grandmaternal Smoking on Body Size and Proportions at Birth

Abstract: Many long-term adverse effects of smoking during pregnancy are known. Increasingly, adverse effects in the grandchild after grandmaternal smoking during pregnancy are reported. We explored this in a birth cohort of 24,000 grandmother–mother–child triads identified from the Finnish Medical Birth Register in 1991–2016. Multiple logistic regression was used to analyze the association between any smoking during pregnancy by both grandmother and mother, or only grandmother or mother on adverse birth outcomes. No sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…[10] In Isabell Rumrich et al study, in Finland 2021, a prospective study to investigate the effect of maternal smoking on body size and body proportions at birth, 24, 000 pregnant-newborns participated from medical birth records in Finland between 1991-2016, where an increased risk of LBW was observed in the newborns of female smokers (OR: 1.25/95%CI) and an increased SGA risk for height and weight (OR: 1.35), while head circumference was statistically less significant (OR: 1.1) and this is consistent with the results of our study and the OR for PI>90th / HLR>90th BBR<10th \ respectively (1.15-1.1-1.26). [11] ‫األبحاث‬ In a meta-analysis conducted by Elise Philips et al in 2020, with the participation of 229, 000 live births in Europe and North America to investigate the relationship between changes in smoking during pregnancy and the risks of adverse pregnancy outcomes and weight gain in adolescence, this analysis concluded that maternal smoking in the first trimester of pregnancy was not associated with adverse birth outcomes compared to non-smokers, and this is inconsistent with the results of our study, while continued smoking was associated with a higher risk of SGA OR: 2.15 (95% CI 2.07-2.23). The analysis also showed that reducing the number of cigarettes consumed between the first and third trimesters of pregnancy without stopping, it was also associated with a higher risk of SGA (OR: 1.89), but lower than women who continued the same amount of cigarettes during pregnancy (OR: 2.20).…”
Section: Discussionmentioning
confidence: 99%
“…[10] In Isabell Rumrich et al study, in Finland 2021, a prospective study to investigate the effect of maternal smoking on body size and body proportions at birth, 24, 000 pregnant-newborns participated from medical birth records in Finland between 1991-2016, where an increased risk of LBW was observed in the newborns of female smokers (OR: 1.25/95%CI) and an increased SGA risk for height and weight (OR: 1.35), while head circumference was statistically less significant (OR: 1.1) and this is consistent with the results of our study and the OR for PI>90th / HLR>90th BBR<10th \ respectively (1.15-1.1-1.26). [11] ‫األبحاث‬ In a meta-analysis conducted by Elise Philips et al in 2020, with the participation of 229, 000 live births in Europe and North America to investigate the relationship between changes in smoking during pregnancy and the risks of adverse pregnancy outcomes and weight gain in adolescence, this analysis concluded that maternal smoking in the first trimester of pregnancy was not associated with adverse birth outcomes compared to non-smokers, and this is inconsistent with the results of our study, while continued smoking was associated with a higher risk of SGA OR: 2.15 (95% CI 2.07-2.23). The analysis also showed that reducing the number of cigarettes consumed between the first and third trimesters of pregnancy without stopping, it was also associated with a higher risk of SGA (OR: 1.89), but lower than women who continued the same amount of cigarettes during pregnancy (OR: 2.20).…”
Section: Discussionmentioning
confidence: 99%
“…Rumrich et al [5] Transgenerational effect of smoking on the newborns birth characteristics Smoking during pregnancy by both grandmother and mother results in higher odds of the newborns having lower body size and proportionality. Grandmaternal smoking during pregnancy adds an excess risk to maternal smoking during pregnancy for negative birth outcomes.…”
Section: Authors Main Focus Main Findingsmentioning
confidence: 99%
“…The paper by Rumrich et al [5] sheds new light on the transgenerational effects of grandmaternal smoking during pregnancy on the newborn's body size and proportions by using data from the Finnish birth register 1991-2016 (N ≈ 24,000). Smoking by the grandmother during her pregnancy but no smoking of her daughter during pregnancy did not associate with the child's body size and proportions.…”
Section: Blanc Et Al [8]mentioning
confidence: 99%